Plasma myostatin is only a weak predictor for weight maintenance in obese adults - Tsioga, Maria; Oikonomou, Dimitrios; Vittas, Spiros; Kalscheuer, Hannes; Roeder, Eva; Wintgens, Karl Florian; Nawroth, Peter Paul; Wolfrum, Christian; Rudofsky, Gottfried (Experimental and clinical endocrinology & diabetes, 2015)
Predicting an individual’s success in a non-surgical weight loss approach is a demanding need since obesity is becoming an epidemic burden. A possible predictive marker is myostatin, a member of the transforming growth factor b superfamily, which has been shown to be an important regulator of muscle homeostasis.
Gesehen am 06.07.2020